Ensiling maize or elephant grass with olive cake: effect on fermentation, chemical composition and aerobic stability of silages - Tierri Nunes Pozada; João Pedro Soares Falson; Yuri Gabriel Prieto Vasconselos; Oséias Iven Heling; Eduardo Festozo Vicente; Jorge Schafhäuser Junior; João Luiz Pratti Daniel; Naiara Caixeta Da Silva; Carlos Henrique Silveira Rabelo (Ciência Rural)
ABSTRACT: Olive cake (OC) is a wet by-product of olive processing that may be used as animal feedstuff. Our objective was to investigate the impact of adding OC on fermentation and aerobic stability of maize and grass silages. Whole-crop maize (326 g dry matter (DM)/kg as fed) and 4 h-wilted elephant grass (229 g DM/kg as fed) were ensiled without (untreated) or with fresh OC (5% as fed basis). Ensiling was performed in experimental silos (n = 3), which remained stored for 99 d. As results, fermentative losses were unaffected by OC (P = 0.17), while the lactic acid concentration decreased (P = 0.02) by 33.7% in silages with OC. The pH of grass silage increased (P < 0.001) by adding OC (4.43 vs. 4.01 in the control), but it did not change the pH in maize silage. The concentration of acetic acid (P = 0.01) decreased by 15.2% in maize silage with OC and increased by 19.4% in grass silage with OC. The ether extract concentration increased (P = 0.02) in maize silage with OC compared to the control, and it was similar between grass silage without and with OC. After feedout, silage aerobic stability was not altered (P ≥ 0.18) by the addition of OC in maize and grass silages. Therefore, a possible fate for OC is to ensile it together maize forage, because there is no impairment of fermentation and aerobic stability of silages. Ensiling OC with grass is not recommended as it worsened the fermentation pattern.